COMPLEMENTATION (STRATEGIES) IN SUNDANESE - Eri Kurniawan (Linguistik Indonesia, 2017)
The chief goals of this paper are two-fold: to lay out a range of complex structures in Sundanese and to assess the extent to which Englebretson’s (2003) claim regarding the absence of complementation in colloquial Indonesian can be extended to Sundanese, a neighboring language typologically related to Indonesian. In his corpus study, Englebretson argues that the colloquial Indonesian lacks (syntactic) complement clauses and two verbs/clauses can be linked via complementation strategies, including verb serialization and nominalization. Examination of Sundanese complex structures reveals that Sundanese does evince syntactic complementation and elements that Englebretson might analyze as framing elements are demonstrably arguments of a predicate. Englebretson’s account therefore cannot be maintained in Sundanese.